Reformas al código de la niñez y adolescencia para evitar que las personas adultas y adultos mayores, sean considerados obligados subsidiarios a la prestación de alimentos - Moreno Saavedra, Kerly Yessenia (2015)
This thesis entitled "Amendments to the Code of Childhood and Adolescence to keep adults and seniors, are considered obligated subsidiary in providing food" is the result of an analysis to Art 69 of the Constitution. of the Republic of Ecuador, where states to protect the rights of members of that family, responsible parenthood be promoted; Mother and father are forced to care, upbringing, education, food, integral development and protection of the rights of their children, especially when they are separated from them for any reason. Also later in the Art. 83 gives the following duties and responsibilities of Ecuadorians aid, support, educate and care for daughters and sons. This duty is responsibility of parents in equal proportion, and correspond to the sons and daughters when mothers and fathers need. These two constitutional provisions at any time sends the grandparents or relatives of older persons minors have the duty and responsibility to cover food and care for their grandchildren when parents can not contribute, therefore, is failed to observe the constitutional rule of rights and justice to the alternative force grandparents to pay alimony, and in some extreme cases have been deprived of their liberty; this violates the rights and guarantees of older persons who are in the focus group. Each parent must answer their direct obligations towards his family, and other family members voluntarily must contribute financially to their maintenance. Therefore the standard outlined in the Code of Childhood and Adolescence is less hierarchy and contradicts the constitutional supremacy. The theoretical and field of this thesis work has allowed me to obtain criteria, with clear and precise basis of well known literature, which contributed to the verification of targets, and testing of the hypothesis, allowing support reforms to the Code of Childhood and Adolescents. The content of this thesis is the result of an arduous legal research of the author in the scientific, legal, social and methodological level, addressing theories and knowledge obtained through techniques and methods